Pengaruh Pemberian Trichoderma sp. Dan Plant Growth Promoting Rhizobacteria (PGPR) Terhadap Pertumbuhan Akar Stek Pucuk Tanaman Krisan (Chrysanthemum morifolium R.) - Musa, Brigita Aprillia; Sumayku, Bertje R.A.; Rantung, Meity R. (Sam Ratulangi University, 2023)
This study aims to determine whether there is an interaction and influence of concentration from the administration of Trichoderma sp. and Plant Growth Promoting Rhizobacteria (PGPR) on the root growth of chrysanthemum plants. This research was carried out at the Center for Protection and Quality Testing of Horticultural Food Crops and the Screen House Office of the Center for Seeds, Agricultural Nurseries and Agrotourism Show Window, Tomohon City. This research was conducted from June to August 2022. Primary data was obtained from the results of the study including the variables root length, root weight, and percentage of living cuttings while secondary data was obtained through books obtained from local bookstores and the internet via Google Scholar in the form of books, articles journals and theses related to research topics. The results showed that the longest plant roots were produced at the concentration level of Trichoderma sp. solubility of 107 and PGPR 15ml/l (T1P3) with an average of 11.6 cm and the heaviest roots were produced at the concentration level of Trichoderma sp. solubility 109 and PGPR 10ml/l (T3P2) with an average of 0.49 gram.